2004
DOI: 10.1007/bf02256548
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil elastase induces IL-8 synthesis by lung epithelial cells via the mitogen-activated protein kinase pathway

Abstract: The sequestration of neutrophils in the lung and the release of proinflammatory mediators, including neutrophil elastase, are responsible for sepsis-induced microvascular permeability and alveolar epithelial cell damage. To assess the underlying mechanism, human neutrophil elastase (0.01-0.5 microg/ml) was added to cultured A549 epithelial cells in the presence or absence of inhibitors. IL-8 was analyzed by ELISA or by RT-PCR to measure the IL-8 synthesis capacity. Mitogen-activated protein kinase (MAPK) activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 30 publications
5
29
1
Order By: Relevance
“…However, LPS-induced neutrophils infiltration of lung was attenuated in the Pre-UTI high group. Previous studies reported that UTI inhibits LPS-induced production of IL-8 in vascular endothelial cells [21], neutrophil elastase-induced IL-8 gene expression [22,23], expression of intercellular adhesion molecule-1, endothelial cell adhesion molecule-1 on endothelial cells, and transendothelial migration of neutrophils stimulated by IL-8 [24]. Also, UTI not only inactivated elastase secreted by neutrophils, but also suppressed the production and secretion of elastase from neutrophils which play an important role of diapedesis and extravasation of granulocytes [21,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…However, LPS-induced neutrophils infiltration of lung was attenuated in the Pre-UTI high group. Previous studies reported that UTI inhibits LPS-induced production of IL-8 in vascular endothelial cells [21], neutrophil elastase-induced IL-8 gene expression [22,23], expression of intercellular adhesion molecule-1, endothelial cell adhesion molecule-1 on endothelial cells, and transendothelial migration of neutrophils stimulated by IL-8 [24]. Also, UTI not only inactivated elastase secreted by neutrophils, but also suppressed the production and secretion of elastase from neutrophils which play an important role of diapedesis and extravasation of granulocytes [21,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The "vehicle" was dimethyl sulfoxide, PBS, or both, or, in different experiments, a solvent control. The doses of reagents used were as follows: thrombin, 0.5 U/mL; collagen, 5 mg/mL; plateletactivating factor (PAF), 0.1 mmol/L; AA, 100 mmol/L; PD98059, 40 mmol/L [36,37]; SB203580, 40 mmol/L [38,39]; and SP600125, 3 mmol/L. Detection of agonist-induced platelet surface P-selectin expression by flow-cytometric analysis and ELISA.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies of the mitogen-activated protein kinase (MAPK) superfamily provide a framework for investigating the response of neutrophil to various stimulators (4). The MAPK can be categorized into 5 subfamilies: the ERK1/2, the p38, the JNK, the ERK5, and the ERK3/4 subfamilies (5).…”
Section: Introductionmentioning
confidence: 99%